Maturation processes in glass-ionomer dental cements - John W. Nicholson (Taylor & Francis Group, 2018)
Glass-ionomer cements are used for a variety of tooth-repair functions in clinical dentistry. They are formed by reaction of a basic glass powder with a solution of polymeric water-soluble acid, usually polyacrylic acid. After the initial neutralization reaction, by which the cement hardens, various maturation reactions occur. Changes induced by these maturation reactions are identified as: increase in strength; reduction in plasticity; improvement in opacity; and increase in proportion of tightly bound water. In addition, in contact with the tooth, an ion-exchange interfacial layer is gradually formed. This is mechanically strong and chemically-resistant. These changes are described in the current paper, which reviews the extent to which they occur, and reports what is know about the chemistry that underlies them. Processes involving slow diffusion of various ions and of water through the set cement bring about these changes. They include a secondary setting reaction to form a phosphate-based phase, binding of water to co-ordination sites around metal cations and to a hydration sheath around the polymer molecules, and possibly reaction of water with glass particle surfaces to form silanol groups. Evidence from a wide range of literature sources is used to be build up a detailed picture of the chemistry of the maturation processes, and gaps in our understanding are highlighted. The article concludes that, given the importance of glass-ionomers in contemporary dentistry, it is important to know the extent to which such maturation processes occur in current cement formulations, and also to determine how rapidly they take place.